PENERAPAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN MOTIVASI BELAJAR IPA SISWA KELAS V SD NEGERI 274 MATTIROWALIE - Muhammad Amran; Sudirman Sudirman; Latri Aras (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This research is a classroom action research that aims to increase student motivation in science subjects of grade V students of SD Negeri 274 Mattirowalie through the application of the Word Square learning model. The subjects of this study were 19 grade V students. The research design used is cyclical or recycled research with four stages, namely, planning, implementing actions, observation and reflection. The data collection techniques used are observation, questionnaires and documentation. The data analysis techniques used are descriptive, qualitative and quantitative. The results showed that there was an increase in students' motivation to learn science from 57.89% in the cycle to 84.21% in second cycle. The conclusion of this study is that the application of the Word Square learning model can increase the motivation to learn science of grade V students of SD Negeri 274 Mattirowalie.